Closed-loop Supply Chain as an Agent of Sustainable Development - Shu-San Gan (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2015)
Sustainability has recently become an important issue which received growing attentions from government, society, industries as well as academia. There have been concerns on relatively rapid growth in population and increased quality of life despite limited natural resources and landfill capacity. Closed-loop Supply Chain (CLSC) is one of many approaches to mitigate the abovementioned disproportion. This article aims to study closed-loop supply chain by explaining the definition, description, pros and contras, relevance, case studies from literature, and potential research; such that its role as an agent of sustainable development can be recognized.